Computerized tomography based evaluation of level I and II axillary lymph nodes by high conventional tangential fields in carcinoma breast - Chandrakant, Lalit; Thakur, Shabnum; Gupta, Manoj; Seam, Rajeev K.; Gupta, Manish; Sharma, Sanjeev (International Journal of Research in Medical Sciences, 2020)
Background: Axillary radiation and surgery have provided equivalent local control in early breast cancer patients. It is believed that tangential field (TF) radiation that was used to treat the breast coincidently delivered radiation treatment to the lower axilla and eradicated the disease. In the era of CT-based three dimensional- (3D) radiotherapy planning, however concerns have been raised about the adequacy of coverage of the axillary levels in the tangential fields. In this study, author evaluated the coverage of the axillary nodal levels I and II using high conventional tangential fields in patients with or without axillary dissection. Methods: A prospective study was conducted which included 18 cases for a period of one year, radiation therapy was planned to the chest wall or whole breast by using the high conventional tangential field using 2D radiation portals. Central lung distance (CLD) and the distance of superior border was measured form the head of the humerus and were recorded. CECT chest was done in the same position alike during conventional simulation. All the images were shifted to the treatment planning system. The Contouring of Axillary lymph nodes level I and II was done on Oncentra contouring software. Results: The coverage of the axillary nodes was not related to central lung distance (CLD). However, some with CLD of 1cm had more coverage of the level I nodes than with CLD of 2 cm and the maximum CLD in the field was 2.5 cm. Of the 18 patients in the study, 13 patients had <2 cm distance from the humeral head and all the axillary level II LN covered in the field. Whereas 5 patients having distance >2 cm did not have adequate coverage of level II axillary LN’s. Conclusions: The distance of the cranial border of the tangent portal from the head of the humerus shows a relationship with coverage of level II nodes cranially. As the distance decreases the coverage of level II nodes cranially keeps increasing. In majority of the patients a distance of 2 cm or less than 2 cm ensured good coverage of level II nodes cranially. Similarly, no correlation was found between volumetric coverage of the axillary nodes with central lung distance.